Persistence of civil wars - Daron Acemoglu; Davide Ticchi; Andrea Vindigni (Institute for the Study of Labor (IZA), 2009)
A notable feature of post-World War II civil wars is their very long average duration. We provide a theory of the persistence of civil wars. The civilian government can successfully defeat rebellious factions only by creating a relatively strong army. In weakly-institutionalized polities this opens the way for excessive influence or coups by the military. Civilian governments whose rents are largely unaffected by civil wars then choose small and weak armies that are incapable of ending insurrections. Our framework also shows that when civilian governments need to take more decisive action against rebels, they may be forced to build over-sized armies, beyond the size necessary for fighting the insurrection, as a commitment to not reforming the military in the future.
urn:nbn:de:101:1-200910122597
Keywords: H2; N10; N40; P16; 330; Civil wars; commitment; coups; military; political transitions; political economy; Bürgerkrieg; Dauer; Innere Sicherheit; Verteidigungshaushalt; Politisches Ziel; Welt